KINERJA PEMERINTAH KECAMATAN DALAM PEMBERIAN REKOMENDASI PENGURUSAN KARTU KELUARGA DI KANTOR CAMAT TANAH PUTIH KABUPATEN ROKAN HILIR - Welasari Welasari (UIR Press, 2018)
The research brings out the issues about the subdistrict government operation in order to give recommendation of family card arrangement in subdistrict office of Tanah Putih Rokan Hilir district is expected capable to give the more easy and efficientservicetosociety. There are some issues, such as: the lack of office facilities, human resource and employees' working culture. The purpose of this research is to describe the government operation and some factors which give influence to the operational itself including the leader commitment, the employees motivation, and societysupport. The information sources of the research are from subdistrict of Tanah Putih, subdistrict secretary, government section, public service section and society in recommending family card arrangement. The techniques of collecting data were doing by natural setting of primer and secondary data sources in interviewing, observating, and documentating ways. The techniques of data analisis in the research held by using interactive model. Which is analyzing data at the same moment while data collecting in progress and after that there are few steps:1. Data collection. Collecting data from interview and observation materials. 2. Data reduction: gaining data from the field research and note them as a detailed summary-only consist of basic research issues because it will give a clear illustration of main research. 3.Data display diplaying data in table, graphic, and chart forms. The data presentation in this research was using narative text. 4. Verifying checking all data and make the summary. It must be supported by valid and consistent data so that it will be a summary with credibility.